2005
DOI: 10.1080/08860220500200262
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Hemodialysis Adequacy by Ionic Dialysance: Comparison to Standard Method of Urea Removal

Abstract: Background. The hemodialysis adequacy is one of the most important issues influencing the survival of patients on maintenance hemodialysis (HD). Assessment of measuring the delivered dialysis dose using clearance  time/volume (Kt/V) index requires multiple blood sampling. New methods for assessment of dialysis dose based on ionic dialysance (ID) have been suggested. Online conductivity monitoring (using sodium flux as a surrogate for urea) allows the repeated noninvasive measurement of Kt/V on each HD treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…Application of such a method into practice worsens patients' satisfaction related to dialysis treatment and also does not eliminate a difference between SPVV urea Kt/V and online Kt/V, although it diminishes it to 1.5% [22]. A better correlation coefficient was also achieved in the study of Rački et al [23] when mean online Kt/V was related to equilibrated Kt/V (r = 0.8959). However, this correlation was much lower (r = 0.2071, P = 0.04) when the individual patient measurements were compared.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Application of such a method into practice worsens patients' satisfaction related to dialysis treatment and also does not eliminate a difference between SPVV urea Kt/V and online Kt/V, although it diminishes it to 1.5% [22]. A better correlation coefficient was also achieved in the study of Rački et al [23] when mean online Kt/V was related to equilibrated Kt/V (r = 0.8959). However, this correlation was much lower (r = 0.2071, P = 0.04) when the individual patient measurements were compared.…”
Section: Discussionmentioning
confidence: 70%
“…However, this correlation was much lower (r = 0.2071, P = 0.04) when the individual patient measurements were compared. The aforementioned data showed that online Kt/V underestimated urea removal by a mean of 6% [23].…”
Section: Discussionmentioning
confidence: 94%
“…Apart from blood sample-based methods, alternative methods determining dialysis dose have been developed, mostly based on measurements of conductivity [4], [5] or of urea [6], recently also of ultraviolet absorbance in the spent dialysate [7]. …”
Section: Introductionmentioning
confidence: 99%
“…Calculation of Kt/V using ionic dialysance without the need for blood samples was proposed as a bedside tool for frequent monitoring of HD, and was proven to be accurate in adults . It is widely used in adult patients on HD, but it has not been evaluated in children receiving HD.…”
Section: Discussionmentioning
confidence: 99%
“…The derived ionic dialysance then represents effective urea clearance from which Kt/V is calculated, allowing for Kt/V to be monitored at every treatment without blood sampling . This approach was found to correlate well with standard urea‐based method in adult patients on HD . Although widely used in adults, use of ionic dialysance has not been reported in pediatric HD.…”
Section: Introductionmentioning
confidence: 95%